Thriving in the dynamics: a multi-level investigation of needs-supportive features, situational motivation, and employees’ subjective well-being - Wang, Zheni; Panaccio, Alexandra (Current Psychology, 2023)
Employees often demonstrate various regulatory intentions toward multiple responsibilities they must fulfill on the job. Therefore, it is possible that employees’ motivation changes during the workday because of the various situations they have experienced and that these motivational fluctuations affect their subjective well-being across different activities. Following the integrated frameworks of the self-determination theory (SDT) and the hierarchical model of motivation (H-SDT), the present research studied the variations of employees’ daily motivation for work across different activities using the survey of day reconstruction method (DRM). Multi-level structural equation modeling (MSEM) was used to analyze the variations in the perceived three basic psychological (i.e., autonomy-, relatedness-, and competence-) needs-supportive features (NSFs), situational motivation, and variables capturing the employees’ subjective well-being (including vitality and positive/negative affect) laid out according to a list of work episodes in DRM. Results of this study confirmed that employees’ subjective well-being (mainly vitality and positive affect) were positively promoted by NSFs pertained to specific work activities via the indirect path of situational autonomous motivation at work. Furthermore, vitality and positive affect were also directly predicted by situational autonomous motivation. These empirical findings expanded the research evidence supporting employees’ subjective well-being as a multi-level and multi-dimensional dynamic motivational consequence promoted by configurable specific NSFs at work. We also discussed the limitations and future directions for this line of research.
Keywords: Dynamics of work motivation; Multi-level modeling; Psychological health; dept.mgt; peer-reviewed